2009
DOI: 10.1007/s10600-009-9223-3
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides and sterols from green algae Caulerpa lentillifera and C. sertularioides

Abstract: Sterols and polysaccharides of green alga Caulerpa lentillifera grown under laboratory conditions and in mariculture and polysaccharides of green alga C. sertularioides grown under natural conditions were studied. The sterol fraction consisted of C 27 -C 29 steroidal alcohols with Δ 5 -unsaturation in the steroid core regardless of the growth conditions. The dominant (79.9%) steroid component of the sterol fraction was clionasterol. The water-soluble fraction of C. lentillifera grown under laboratory condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…In Western-Pacific region, it is mainly distributed in the South China Sea. In this algae, plenty of polysaccharides and sterols are found that could be an ideal natural bait for fish (Shevchenko et al 2009). It has also been reported that extracts from this algae can elicit pronounced antinociceptive and anti-inflamatory activity (Brito da Matta et al 2011), antibacterial, and antivirus activity (Zandi et al, 2006;Darah et al 2014;Esquer-Miranda et al 2016).…”
Section: Chloroplast Genome;mentioning
confidence: 99%
“…In Western-Pacific region, it is mainly distributed in the South China Sea. In this algae, plenty of polysaccharides and sterols are found that could be an ideal natural bait for fish (Shevchenko et al 2009). It has also been reported that extracts from this algae can elicit pronounced antinociceptive and anti-inflamatory activity (Brito da Matta et al 2011), antibacterial, and antivirus activity (Zandi et al, 2006;Darah et al 2014;Esquer-Miranda et al 2016).…”
Section: Chloroplast Genome;mentioning
confidence: 99%
“…While C. sertularioides shown the ability to inhibit free radicals more than 10 percent compared to red algae and brown algae. [13] In addition, the oligosaccharide extracted from C. racemose, was also found in the form of α-(14) glucose after being hydrolyzed, and have been classified as gluco-oligosaccharides which can be a good source of carbohydrates for bacteria to grow. [10], [14] Furthermore, it had been reported that Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…And it exhibited approximate effect of aspirin (Arenajo et al, 2017). Shevchenko et al (2009) extracted three polysaccharide fractions, water-soluble P1, P2 and base-soluble P3. The molecular weights of these polysaccharides were 20-60 KDa, 20-40 KDa and more than 70 KDa, respectively.…”
Section: Bioactive Components Of C Lentillifera and Their Biologicalmentioning
confidence: 99%